Castable polyurethane elastomers - Clemitson, Ian (CRC Press, Taylor & Francis Group, 2015)
Currently, raw material suppliers are the sole providers of polyurethane processing information. In most cases, they give instruction only on how to mix products and do not always include an explanation of the accompanying logic as to why these recommendations are being made. Castable Polyurethane Elastomers explains the production process of polyurethane components from both the theoretical and practical point of view. It describes the underlying concepts for the raw material supplier recommendations and explains how to achieve application-specific properties in polyurethane.